PENERAPAN METODE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPA KELAS V SD NAHDLATUL ULAMA METRO - Choirunnisa, Silvi; Amrulloh, Hanif; Laili, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ critical thinking skills through the implementation of the Teams Games Tournament (TGT) learning method in science (IPA) subjects for fifth-grade students at SD Nahdlatul Ulama Metro. The background of this study is the low level of students’ critical thinking skills, which is indicated by their limited ability to analyze problems, express opinions, and draw conclusions, as learning is still predominantly teacher-centered. This research employed a Classroom Action Research (CAR) design conducted in two cycles, where each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were all fifth-grade students, totaling (adjust the number of students). Data were collected through tests to measure students’ critical thinking skills, observations to assess students’ learning activities, and documentation as supporting data. The data were analyzed using both quantitative descriptive and qualitative approaches by comparing the results from each cycle. The results showed that the implementation of the TGT method significantly improved students’ critical thinking skills. This improvement was indicated by the increase in the average scores and the percentage of learning mastery from the pre-cycle to cycle I, and further improvement in cycle II. In addition, students’ learning activities also increased, as reflected in their active participation in discussions, confidence in expressing opinions, and ability to collaborate effectively in groups. Improvements made in each cycle, particularly in time management and group organization, also contributed to the success of the implementation. Therefore, the Teams Games Tournament (TGT) method is proven to be effective in enhancing students’ critical thinking skills in elementary science learning.